Concentrating on the Fall of the Labor Share - David H. Autor; David Dorn; Lawrence F. Katz; Christina Patterson; John Van Reenen (Center for Economic Studies and ifo Institute (CESifo), 2017)
The recent fall of labor's share of GDP in numerous countries is well-documented, but its causes are poorly understood. We sketch a “superstar firm” model where industries are increasingly characterized by “winner take most” competition, leading a small number of highly profitable (and low labor share) firms to command growing market share. Building on Autor et al. (2017), we evaluate and confirm two core claims of the superstar firm hypothesis: the concentration of sales among firms within industries has risen across much of the private sector; and industries with larger increases in concentration exhibit a larger decline in labor's share.
Keywords: 330